2011
DOI: 10.1080/01634372.2010.543263
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Difference Between Aging and Disability Service Systems Consumers: Implications for Policy Initiatives to Rebalance Long-Term Care

Abstract: This study explores service professionals' perceptions of how and why older adults and younger persons with disabilities are different consumers and clients within the long-term care service sector. Data are from 2004, early in the history of federal long-term care rebalancing initiatives, reflecting perceptions at that time. Findings suggest professionals working within aging, developmental disability, and physical disability service networks believe significant distinctions exist related to age of clients an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 5 publications
1
13
0
Order By: Relevance
“…5 Many require health services and other long term services and supports that can be difficult to access in sufficient quality and quantity. 9, 10 They are also at risk of falling between the cracks of an aging services system that is not well prepared to serve younger adults with disabilities and a disability services system that is not well prepared to help them to age successfully, 11 Fortunately, this is starting to be corrected by integrating aging and disability services. 12 …”
Section: Introductionmentioning
confidence: 99%
“…5 Many require health services and other long term services and supports that can be difficult to access in sufficient quality and quantity. 9, 10 They are also at risk of falling between the cracks of an aging services system that is not well prepared to serve younger adults with disabilities and a disability services system that is not well prepared to help them to age successfully, 11 Fortunately, this is starting to be corrected by integrating aging and disability services. 12 …”
Section: Introductionmentioning
confidence: 99%
“…The early stages of this transition were facilitated by policy responses to issues of inefficiency (Lee, Bott, Gajerski, & Taunton, 2009) and quality (US General Accounting Office, 2003) of nursing home care, as well as consumer preference to receive care within their own homes (Kelly, Knox, & Gekoski, 1998). Such policies include the Omnibus Reconciliation Act of 1981, the US Supreme Court Olmstead decision in 1999, and the New Freedom Initiative of 2001; all of which increased access to HCBS as an alternative to institutional care for individuals with disabilities (Putnam, 2011). HCBS allow adults who are nursing-home-eligible to receive health, support, and homemaker services within their own homes (Zarit, Stephens, Townsend, Greene, & Leitsch, 1999) and have demonstrated numerous benefits, such as reducing the risk of admission into institutional care (Burr, Mutchler, & Warren, 2005) and mortality (Albert, Simone, Brassard, Stern, & Mayeux, 2005).…”
Section: Movement Toward Consumer Direction In Long-term Care Policymentioning
confidence: 97%
“…In practice, these distinctions can manifest in differential approaches to serving consumers. Putnam (2011) found that providers for individuals with disabilities view clients' needs differently based on their life stage, emphasizing social integration and productivity in goals for younger and middle-aged individuals, but goals for older adults with disabilities focus on avoiding institutionalization during retirement years. The same study reported that providers also hold views of clients' interests that reflect age-related stereotypes.…”
Section: Lack Of Advocacy For CD By Older Adultsmentioning
confidence: 98%
“…Even for those who have this dual experience, the lack of research relating to aging with disability and LSS remains problematic, particularly as LTSS professionals tend to think of older adults and younger persons aging with disability as qualitatively different consumers with differing aging-related needs. 8 Fostering new knowledge development and knowledge translation can help to answer important global questions about providing LTSS to persons aging with disability such as: How does aging with long-term disability differ from aging into disability in later life? What types of LTSS do persons aging with disabilities need that are not currently found within existing aging or disability networks?…”
Section: Building Capacity In Ltss To Support Persons Aging With Disamentioning
confidence: 99%